Analysis speed of junior sprint athletes of PASI (Persatuan Atletik Seluruh Indonesia) Banjarbaru city - Amirudin, Akhmad; Perdinanto, Perdinanto; Rahmadi, Rahmadi; Latifah, Nur (Universitas Suryakancana, 2025)
This study aims to analyze the sprint speed performance of junior athletes from the Indonesian Athletics Association (PASI) in Banjarbaru City. Speed is a fundamental component of physical fitness that plays a crucial role in sprinting events, especially for young athletes who are in a critical phase of motor and physiological development. This research employed a descriptive quantitative method with total sampling involving 17 junior athletes. The primary instrument was a 60-meter sprint test, conducted twice with the best result used for data analysis. The recorded times were categorized according to established sprint assessment norms and analyzed using percentage distribution. The results showed that 52.94% of athletes fell into the Fair category, 35.29% were in the Poor category, and 11.76% were classified as Very Poor. Notably, no athletes were categorized as Good or Very Good. These findings indicate that the overall sprint speed of junior PASI Banjarbaru athletes remains at a moderate to low level, insufficient for higher-level competition. Contributing factors include suboptimal starting techniques, underdeveloped muscle strength, and the lack of scientifically-based and varied training methods. Therefore, a more structured, systematic training program tailored to the developmental characteristics of young athletes is essential to optimize their sprinting potential. This study is expected to serve as a foundation for evaluating and designing more effective training strategies focused on performance improvement for junior athletes in Banjarbaru.